2014
DOI: 10.1186/1478-811x-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic T cell protein-tyrosine phosphatase deficiency ameliorates cerulein-induced acute pancreatitis

Abstract: BackgroundAcute pancreatitis (AP) is a common clinical problem whose incidence has been progressively increasing in recent years. Onset of the disease is trigged by intra-acinar cell activation of digestive enzyme zymogens that induce autodigestion, release of pro-inflammatory cytokines and acinar cell injury. T-cell protein tyrosine phosphatase (TCPTP) is implicated in inflammatory signaling but its significance in AP remains unclear.ResultsIn this study we assessed the role of pancreatic TCPTP in cerulein-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
2
11
0
1
Order By: Relevance
“…Of note, panc-TCPTP KO mice exhibit a phenotype that is comparable with obese glutathione peroxidase 1-deficient mice which display defective insulin secretion associated with oxidation of PTPs (including TCPTP) and decreased PDX1 and insulin content [40]. Further, we recently demonstrated beneficial effects of pancreatic TCPTP deficiency in mitigating cerulein-induced acute pancreatitis [23], highlighting the diverse functions of TCPTP in the exocrine and endocrine pancreas. Finally, the finding that the metabolic effects of pancreatic TCPTP deficiency are influenced by diet are relevant to human type 2 diabetes, which is known to correlate with old age and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, panc-TCPTP KO mice exhibit a phenotype that is comparable with obese glutathione peroxidase 1-deficient mice which display defective insulin secretion associated with oxidation of PTPs (including TCPTP) and decreased PDX1 and insulin content [40]. Further, we recently demonstrated beneficial effects of pancreatic TCPTP deficiency in mitigating cerulein-induced acute pancreatitis [23], highlighting the diverse functions of TCPTP in the exocrine and endocrine pancreas. Finally, the finding that the metabolic effects of pancreatic TCPTP deficiency are influenced by diet are relevant to human type 2 diabetes, which is known to correlate with old age and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that TCPTP modulates ER stress in MIN6 beta cells and that alterations in pancreatic TCPTP expression may serve to mitigate chronic ER stress [22]. More recently, we reported that pancreatic TCPTP deficiency mitigates cerulein-induced acute pancreatitis in mice [23]. In the current study, we investigated the endocrine role of pancreatic TCPTP and its underlying molecular mechanism.…”
Section: Introductionmentioning
confidence: 92%
“…62 Of note, PTP1B expression during the early stages of AP is comparable to that of other PTPs, such as SHP1, SHP2, 15,16 and TCPTP. 18 However, pancreatic TCPTP deficiency mitigates cerulein-induced AP in mice 18 compared with the effects of PTP1B deficiency observed herein. Thus, additional investigations into the regulation of PTPs and their contribution to AP pathogenesis are warranted.…”
Section: Discussionmentioning
confidence: 57%
“…16,17 Moreover, T-cell protein tyrosine phosphatase (TCPTP) expression increases in the early stages of the disease, and pancreatic TCPTP deficiency mitigates cerulein-induced AP in mice. 18 These studies implicate PTPs in AP, but additional investigation into the contribution of these enzymes to disease pathogenesis is warranted.…”
mentioning
confidence: 99%
“…In a study suggestive of a new target for pancreatitis treatment, T-cell protein tyrosine phosphatase (TCPTP) is found to be induced in acinar cells during acute pancreatitis [23]. Genetic ablation of TCPTP reduced the severity of acute pancreatitis as measured by serum levels of digestive enzymes.…”
Section: Er Stress and Autophagymentioning
confidence: 99%